Analysis Of Characteristics And Applications Of Modern And Portable Concrete In Sufficient Construction - Yuhuan, Zhao; Al-odaini, Aiman (Journal of Neonatal Surgery, 2025)
Sustainable building innovations, such as research into the qualities and applications of high-performance and lightweight concrete, are summarized using citation-context and the paper's content model. The absence of critical context is the main reason why citation-based scientific summaries fail time and time again. While the construction industry provides the basis for our assessment dataset, the generalizability of our approaches makes them relevant to a wide range of disciplines. Innovations in sustainable building are at a crossroads; they must advance global prosperity while also decreasing their impact on the environment. The construction industry is now at a turning point; it has the power to contribute to global prosperity or damage the environment. Using high-performance, lightweight concrete might be the solution if this issue continues. In addition to making building operations more sustainable, this material drastically reduces the carbon footprint. In light of the urgent need for environmentally friendly alternatives to traditional construction methods, this study seeks to explore the potential consequences of this trend. Some of the advantages of high-performance plus lightweight concrete are that it is more versatile, weighs less, improves thermal insulation, and reduces carbon emissions. Notable projects that use these innovative materials and advocate for green construction practices include the 3D-printed concrete bridge in Amsterdam and the Bosco Vertical in Milan. Research, regulatory support, education, and stakeholder involvement are all necessary for the building industry to fully embrace this technology, according to the report. Based on the findings of this study, it may be feasible to have both development and environmental care simultaneously. Traditional construction methods have a significant influence on the environment.